Bioactive natural products in COVID-19 therapy - Wang, Zhonglei; Wang, Ning; Yang, Liyan; Song, Xian-qing (Frontiers in Pharmacology, 2022)
The devastating COVID-19 pandemic has caused more than 6 million deaths worldwide during the last 2 years. Effective therapeutic agents are greatly needed, yet promising magic bullets still do not exist. Numerous natural products (cordycepin, gallinamide A, plitidepsin, telocinobufagin, and tylophorine) have been widely studied and play a potential function in treating COVID-19. In this paper, we reviewed published studies (from May 2021 to April 2022) relating closely to bioactive natural products (isolated from medicinal plants, animals products, and marine organisms) in COVID-19 therapy in vitro to provide some essential guidance for anti-SARS-CoV-2 drug research and development.